KONSEP PENDIDIKAN SEUMUR HIDUP BERDASARKAN Q.S ALI IMRAN AYAT 190 DAN IMPLIKASINYA TERHADAP PENDIDIKAN AGAMA ISLAM - Yarhami Fadillah; Saripuddin Napitupulu, Charles (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Education is the main capital that must be owned by every human being. Education will elevate humans and humble other humans, humans will be considered valuable if they have an education that is useful for others. Lifelong learning is continuous and continuous learning (continuinglearning) from the cradle to the end of life, in line with the phases of development in humans. Because each phase of development in each individual must be passed by learning in order to fulfill the tasks of development, then learning begins from childhood to adulthood and even until the end of his life.The period of education is very long, many people think that education takes place only at school, but in reality education lasts a lifetime through experiences lived in his life. In the world of Islamic education, it is known as lifelong education or lifelong education. This shows that education takes place indefinitely, starting from birth until we die. So it is clear that lifelong education is very true in our lives. Because if it is out of date, it is easy to be fooled by others. That's why lifelong learning is so important. In addition, Islam also teaches to study His words, both qouliyah, namely verses on the Mushaf Al-Qur'an, as well as kauniyah verses or events in the surrounding nature. So departing from this background, the author is moved to find out what kind of lifelong education values are taught in the Quran surah Ali Imran verse 190. In addition, the author also wants to prove that lifelong education is not only more discussed by western thinkers. To actualize the above problems, it takes the ability and quality of humans, namely the quality of faith and piety, then the quality of science and technology to be able to process and function the potential given by ALLAH SWT to humans.